Nursing of a patient with postsurgical gastroparesis syndrome treated with acupoint application combined with moxibustion (穴位贴敷联合艾灸疗法治疗1例胃癌术后胃瘫综合征患者的护理体会) - LIU Fei (刘菲) (中西医结合护理)
This paper summarized integrated traditional Chinese and western medicine treatment and nursing of patient with postsurgical gastroparesis syndrome. Changes in the patient’s condition were assessed and analyzed, and a comprehensive treatment plan including acupoint application combined with moxibustion, dietary guidance, gastrointestinal decompression, psychological care and other interventions were carried out to relieve the symptom of stomach fullness and improve the early rehabilitation of gastrointestinal function. (本文总结1例胃癌术后胃瘫综合征患者的中西医结合治疗及护理体会。患者入院后完善护理评估, 根据患者的病情变化, 及时调整干预方案, 采用穴位贴敷联合艾灸疗法干预, 并配合饮食指导、胃肠减压护理、心理疏导等常规护理措施, 有效缓解患者胃脘痞满症状, 促进患者早期恢复正常饮食。)